Socio-Demographic indicators of venezuelan migrant population in Ecuador and elements for a public policy, 2015-2022 - Varela Enríquez, Marcelo (2024)
This article's econometric approach to socio-demographic indicators from the National Institute of Statistics and Census, such as births, deaths and hospital discharges of the Venezuelan population in Ecuador between 2015 and 2022, shows a notable impact on the migratory balance of this community. The sustained growth of Venezuelan migrants in the country underlines the importance of designing public policies that address the evidence of the data obtained and apply a human rights approach. The study shows that one of the most urgent needs of this population is access to public health.